Tianeptine in the treatment of patients with arterial hypertension and depression - G. V. Semke; V. F. Mordovin (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study tianeptine monotherapy effects on circadian blood pressure profile (CBPP) and lipid profile (LP) in patients with arterial hypertension (AH) and depression.Material and methods. Seventeen 34-50-year-old patients with AH (Stage I mostly) and anxiety-depressive disorders (ADD), were administered tianeptine for three months.Results. ADD severity was linked to CBPP parameters. Three-month tianeptine therapy significantly reduced anxiety and depression severity, BP level and BP time load parameters, without any negative effects on LP.Conclusion. Adding tianeptine to complex treatment of AH and ADD patients was pathogenetically sensible and could substantially improve antihypertensive therapy effectiveness.